Edukasi Pajak Dan Literasi Keuangan: Kunci Meningkatkan Kesadaran Pajak Di Kalangan Generasi Muda - Lukmawati, Putri Puji; Halawa, Irena Mei Darnis; Rahmadi, Silvia; Linawati, Linawati (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2024)
This study aims to analyze the influence of Tax Education and Financial Literacy on Tax Awareness among young people. Data were collected through a survey of 100 respondents using structured questionnaires and analyzed using multiple linear regression methods. This research employs a quantitative approach, and the data were processed using SPSS version 27. The results indicate that both tax education and financial literacy, individually and simultaneously, have a positive and significant influence on tax awareness, with tax education contributing more dominantly. These findings support the framework of the Theory of Planned Behavior (TPB), which explains that tax education shapes positive attitudes toward taxes, while financial literacy strengthens perceived behavioral control. The study offers practical implications, including recommendations for tax authorities to maximize digital-based tax education programs and collaborate with educational institutions to enhance financial literacy among young people.